KREATIFITAS MENGAJAR GURU DALAM PENINGKATAN MOTIVASI BELAJAR SANTRI MASA KENORMALAN BARU DI MA PONPES DARUNNAJAH JAKARTA - Wicaksono, Tanri (PMPP Lembaga Penelitian dan Studi Kebijakan, 2023)
This study aims to determine how to increase student learning motivation through teacher teaching creativity. In this study the authors used a qualitative descriptive method, and data collection in this study by interviewing several key information, namely principals, students, and classroom teachers.Based on the results of the study, that Teacher Teaching Creativity in increasing student learning motivation is the habituation of the teacher in preparing learning programs, namely making RPP (Learning Implementation Plans) or in the Darunnajah Islamic Boarding School environment called i'dad. The lesson plans include basic competencies, core competencies, learning objectives, learning materials, time allocation and evaluation. A learning program or lesson plan is prepared by the teacher a maximum of one day before the teaching and learning process is carried out. The next creativity is Implementing Learning Programs. In the implementation of the learning program the teacher must perform several stages. First, choosing different learning models and methods. Broadly speaking, MA Darunnajah teachers use the Discovery Learning and MainMapping learning models with the average learning methods in the form of lectures, discussions, and questions and answers. The second creativity is that the teacher is able to manage the class well, in this case the MA Darunnajah Jakarta teacher manages the average class by using the U letter sitting position and forms a circle, Third, the teacher's creativity in using learning media, on average the MA Darunnajah Jakarta teacher uses several Learning media in this new normal include WhatsApp, Google Classroom, YouTube, Email, PPT, and other teaching aids available in various school laboratories. Students' Learning Motivation in the New Normal Period at MA Darunnajah Jakarta also received a good response and increased motivation seen from several aspects, namely, student attendance, task execution and perseverance in learning